A comparative mineralogical and geochemical study of manganese deposits in the Postmasburg Manganese Field, South Africa - Thokoa, Mamello (Rhodes University, Faculty of Science, Department of Geology, 2020)
The Postmasburg Manganese Field (PMF), located in the Northern Cape Province of South Africa, is host to some of the largest deposits of iron and manganese metal in the world. These deposits are restricted to a geographical area known as the Maremane Dome, an anticlinal structure defined by folded dolostones of the Campbellrand Subgroup and overlying ironformations of the Asbestos Hills Subgroup of the Neoarchaean-Palaeproterozoic Transvaal Supergroup. Manganese ores associated with the Maremane Dome have been divided into two major classes in the literature: the Wolhaarkop breccia-hosted massive ores of the Eastern Belt, as well as the shale-associated ores of the Western Belt. The Eastern Belt ores have been classed as siliceous in nature, while the Western Belt deposits are reported to be typically ferruginous. These divisions were made based on their varying bulk chemical and mineralogical compositions in conjunction with their different stratigraphic sub-settings. Presently, both deposit types are explained as variants of supergene mineralisation that would have formed through a combination of intense ancient lateritic weathering in the presence of oxygen, extreme residual enrichments in Mn (and Fe), and accumulations in karstic depressions at the expense of underlying manganiferous dolostones. This study revisits these deposits and their origins by sampling representative end-member examples of both Eastern Belt and Western Belt manganese ores in both drillcore (localities Khumani, McCarthy and Leeuwfontein), and outcrop sections (locality Bishop). In an attempt to provide new insights into the processes responsible for the genesis of these deposits, the possibility of hydrothermal influences and associated metasomatic replacement processes is explored in this thesis. This was achieved using standard petrographic and mineralogical techniques (transmitted and reflected light microscopy, XRD , SEM-EDS and EMPA), coupled with bulk-rock geochemical analysis of the same samples using a combination of XRF and LAICP- MS analyses. Combination of field observations, petrographic and mineralogical results, and geochemical data allowed for the re-assessment of the different ore types encountered in the field. Comparative considerations made between the bulk geochemistry of the different end-member ore types revealed no clear-cut compositional distinctions and therefore do not support existing classifications between siliceous (Eastern Belt) and ferruginous (Western Belt) ores. This is supported by trace and REE element data as well, when normalised against average shale. The geochemistry reflects the bulk mineralogy of the ores which is broadly comparable, whereby braunite and hematite appear to be dominant co-existing minerals in both Eastern Belt (Khumani) and Western Belt (Bishop) ore. In the case of the McCarthy locality, manganese ore is cryptomelane-rich and appears to have involved recent supergene overprint over Eastern Belt type ore, whereas the Leeuwfontein ores are far more ferruginous than at any other locality studied and therefore represent a more complex, hybrid type of oxide-rich Mn mineralisation (mainly bixbyitic) within massive hematite iron ore. In terms of gangue mineralogy, the ores share some close similarities through the omnipresence of barite, and the abundance of alkalirich silicate minerals. Eastern Belt ores contain abundant albite and serandite whereas the main alkali-rich phase in Western Belt ores is the mineral ephesite. In both cases, Na contents are therefore high at several wt% levels registered in selected samples. The afore-mentioned alkali enrichments have been variously reported for both these deposit types. The occurrence of high alkalis cannot be explained through classic residual or aqueous supergene systems of ore formation, as proposed in prevailing genetic models in the literature. Together with the detection of halogens such as F and Br through SEM-EDS analyses of ore from both belts, the alkali enrichments suggest possible hydrothermal processes of ore formation involving circulation of metalliferous sodic brines. Selected textural evidence from samples from both ore belts lends support to fluid-related models and allow the proposal for a common hydrothermal-replacement model to have been responsible for ore formation across the broader Maremane Dome region.
Keywords: Manganese ores -- South Africa -- Postmasburg; Geology -- South Africa -- Postmasburg